Kepastian Hukum Putusan Komisi Pengawas Persaingan Usaha Dalam Penegakan Hukum Persaingan Usaha - Gloria Damaiyanti Sidauruk (Universitas Islam Indonesia, 2021)
This study aims to determine the juridical obstacles related to the implementation of the Decisions of the Business Competition Supervisory Commission (KPPU) in the context of realizing legal certainty and how the role of KPPU should be in implementing its decisions to realize legal certainty in law enforcement of business competition in Indonesia. This is a normative juridical research with statutory, conceptual and comparative approaches. The result of the research is fiest, that the juridical obstacle to the implementation of the KPPU decision in enforcing the law on business competition is Law no. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition has not clearly regulated the KPPU institutions, the KPPU decision is filed for legal action, the cancellation of the KPPU's decision, submission of the KPPU decision to investigators, and KPPU does not have the authority to execute. This weakness causes the KPPU decision to not reflect and realize full legal certainty. Second, the role that KPPU should have is having the authority to investigate, search, and confiscate in conducting examinations of business competition cases. In addition, it is necessary to establish a Special Court for Business Competition, as well as to cooperate with judicial institutions, law enforcement agencies and government agencies to strengthen law enforcement carried out by KPPU in order to create legal certainty through KPPU decisions.Key Words: Business competition; business competition supervisory commission; legal certaintyAbstrakPenelitian ini bertujuan untuk mengetahui hambatan yuridis terkait pelaksanaan Putusan Komisi Pengawas Persaingan Usaha (KPPU) dalam rangka mewujudkan kepastian hukum dan bagaimana seharusnya peranan KPPU dalam pelaksanaan putusannya untuk mewujudkan kepastian hukum dalam penegakan hukum persaingan usaha di Indonesia. Penelitian ini merupakan penelitian yuridis normatif dengan pendekatan perundang-undangan, pendekatan konseptual dan pendekatan perbandingan. Hasil penelitian menyimpulkan, pertama, bahwa hambatan yuridis pada pelaksanaan putusan KPPU dalam penegakan hukum persiangan usaha yaitu Undang-Undang No. 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat belum mengatur kelembagaan KPPU dengan jelas, putusan KPPU diajukan upaya hukum, pembatalan putusan KPPU, penyerahan putusan KPPU kepada penyidik, serta KPPU tidak memiliki kewenangan eksekusi. Kelemahan tersebut menyebabkan putusan KPPU belum mencerminkan dan mewujudkan kepastian hukum secara penuh. Kedua, peranan yang seharusnya dimiliki KPPU yakni memiliki kewenangan penyidikan, penggeledahan, dan penyitaan dalam melakukan pemeriksaan perkara persaingan usaha. Selain itu, perlu dibentuknya Pengadilan Khusus Bidang Persaingan Usaha, serta melakukan kerja sama dengan lembaga peradilan, lembaga penegak hukum dan instansi pemerintah untuk memperkuat penegakan hukum yang dilakukan KPPU agar tercipta kepastian hukum melalui putusan KPPU.Kata Kunci: Kepastian hukum; komisi pengawas persaingan usaha; persaingan usaha